2005
DOI: 10.1063/1.1996928
|View full text |Cite
|
Sign up to set email alerts
|

A model for the formation of “optimal” vortex rings taking into account viscosity

Abstract: The evolution of a viscous vortex ring from thin to thick-cored form is considered using an improved asymptotic solution, which is obtained after impressing a spatially uniform drift on the first-order solution of the Navier–Stokes equations. The obtained class of rings can be considered as the viscous analog solution to the Norbury vortices and classified in terms of the ratio of their initial outer radius to the core radius. The model agrees with the reported theoretical and experimental results referring to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
60
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(62 citation statements)
references
References 18 publications
2
60
0
Order By: Relevance
“…While in the present case vortex growth was extended until T*Ϸ8, recent theoretical studies suggest that vortex formation can, in principle, be extended by another 35%, approaching T*Ϸ11 (Kaplanski and Rudi, 2005). This room for improvement may already be occupied by jetters whose performance is known to surpass that of Nemopsis bachei, such as Aglantha digitale (Colin and Costello, 2002).…”
Section: Discussionmentioning
confidence: 53%
“…While in the present case vortex growth was extended until T*Ϸ8, recent theoretical studies suggest that vortex formation can, in principle, be extended by another 35%, approaching T*Ϸ11 (Kaplanski and Rudi, 2005). This room for improvement may already be occupied by jetters whose performance is known to surpass that of Nemopsis bachei, such as Aglantha digitale (Colin and Costello, 2002).…”
Section: Discussionmentioning
confidence: 53%
“…Weigand & Gharib (1997) have shown that an appropriate choice of these constants leads to a close match to (1.3) with their original experimental data and the results of rigorous numerical analysis by Stanaway et al (1988). Both experimental data reported by Weigand & Gharib (1997) and the model by Kaplanski & Rudi (2005) predict the Gaussian distribution of the vorticity in the vortex ring. Also, it was shown that the formulae obtained in the limit of small vortex ring Reynolds numbers can be applicable for the description of vortex rings with realistic values of these numbers (see Fukumoto & Kaplanski 2008).…”
Section: Introductionmentioning
confidence: 85%
“…An approximate, linear first-order solution of the Navier-Stokes equation for the axisymmetric geometry and arbitrary time was reported by Kaltaev (1982), Berezovski & Kaplanski (1995) and Kaplanski & Rudi (1999). Based on this solution, Kaplanski & Rudi (2005) derived an expression for the translational velocity of the vortex ring for arbitrary times. In the limit of small and large times this expression reduces to those described by (1.1) and (1.2) respectively (Kaplanski & Rudi 1999;Fukumoto & Kaplanski 2008).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Therefore, there is room for improvement of our understanding of the relationship between the perturbation response of models for isolated vortex rings and dipoles, and the pinch-off phenomenon observed in laboratory Rows and in the field, by considering more realistic models for che vonices. ln two dimensions, more realistic vortex models with continuous distributions of vorticity have been previously studied by Boyd & Ma ( 1990), Kizner & Khvoles (200.t ), Khvoles,Berson & Kizner (200.5 ) and Albrecht, Elcrat & Miller (2011 ), and others; whereas Kaplanski & Rudi (2005) and Fukumoto & Kaplanski (2008) have considered similar models for vortex rings. Unlike the inviscid solutions of Norbury ( 1971) andPierrehumbert ( 1980), these models were viscous and studying their perturbation response required the use of viscous flow solvers.…”
Section: Introductionmentioning
confidence: 99%